Gerakan Bersama Aksi Bergizi Untuk Mencegah Stunting Di SMK Islam Farmasi Sumbawa - Nur Arifatus Sholihah; Asri Reni Handayani; Ana Lestari; Herni Hasifah; Kusriawansyah Kusriawansyah (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
This service aims to provide information through the joint movement of nutritious action to prevent Stunting at SMK Islam pharmacy Sumbawa. The results of this activity are expected to be able to raise awareness early on to the community, especially teenagers of advanced school age about the importance of practicing healthy living behaviors and taking blood-adding tablets regularly and on a scheduled basis.